Sensemaking after failure. Which prisoners are learning from their failures? - Szczurek, Marek (My University, 2012)
The study aimed to investigate the response to the failure. How do people make sense about their life failures, and whether to draw conclusions and learn from them. The object of study beyond the creation of meaning about their failures was also determined whether the level of self-actualization and motivation has an impact on the process of sensemaking and the location of guilt. Sensemaking theory proposed by Karl Weick was the theoretical basis for this study. The study was conducted with six prisoners, interviewed by Dan P. McAdams Script - The life story interview. Then the subjects completed the Self-Actualization Questionnaire KSAS proposed by Zenon Uchnast. Studies show that prisoners are learning from their failures and trying to build new strategies. Research has also shown that there is a correlation between the level of self-actualization and the motivation and learning from life failures.

Przeprowadzone badania miały na celu zbadanie reakcji na poniesioną porażkę. Jak ludzie szukają i jak tworzą poczucie sensu w swoich życiowych porażkach oraz czy wyciągają z nich wnioski i uczą się poprzez nie. Przedmiotem badania poza tworzeniem sensu na temat swoich porażek było również określenie, czy poziom aktualizacji siebie, oraz motywacja ma wpływ na proces tworzenia sensu i umiejscowienie winy. Teoria tworzenia sensu zaproponowana przez Karla Weick’a była podstawą teoretyczną poniższej pracy. Badania zostały przeprowadzone z sześcioma więźniami, z którymi przeprowadzono wywiad według skryptu Dan P. McAdams - The life story interview. Następnie osoby badane wypełniły Kwestionariusz Stylów Samo-aktualizacji Siebie KSAS zaproponowany przez Zenona Uchnasta. Z przeprowadzonych badań wynika, że więźniowie uczą się ze swoich porażek i starają się na ich podstawie budować nowe strategie działania. Badania wykazały również, że istnieje związek pomiędzy poziomem aktualizacji siebie i motywacją a uczeniem się ze swoich życiowych porażek.
Nadawanie znaczenia porażce. Którzy więźniowie uczą się na swoich błędach?
Keywords: psychologia; sens życia; więźniowie; resocjalizacja; porażka